Social support and frailty progression in community-dwelling older adults - Muhammad Helmi Barghouth; Jessica Klein; Tim Bothe; Natalie Ebert; Elke Schaeffner; Nina Mielke (Frontiers Media S.A., 2024)
ObjectivesDespite the growing evidence regarding the influence of social factors on frailty in older adults, the effect of social support remains unclear. This study aims to assess the association between social support and frailty progression (transition and incidence) in a sample of community-dwelling older adults.MethodsUsing a cohort study design, 1,059 older adults from the Berlin Initiative Study were followed up for 2.1 years. Multinomial and logistic regression analyses were performed to assess the association of social support using Oslo Social Support Scale-3 with frailty transition and incidence, respectively. Gender differences were explored using stratified analyses.ResultsAt baseline, frailty prevalence in the study population [mean (SD) age 84.3 (5.6) years; 55.8% women] reached 33.1% with 47.0, 29.4 and 23.6% of the participants reporting moderate, strong and poor social support, respectively. Over the follow-up period, social support was not significantly associated with the frailty transition categories in the adjusted model. Conversely, the adjusted logistic regression analysis showed that participants with poor social support had twice the odds of becoming frail compared to those with strong social support (OR 2.07; 95% CI 1.08-3.95). Gender-stratified analyses showed comparable estimates to the main analysis but were statistically non-significant.DiscussionOur study results underpin the role of social factors in frailty incidence and highlight social support as a potential target for frailty-preventing interventions in older adults. Therefore, it is important to adopt a biopsychosocial model rather than a purely biomedical model to understand and holistically improve the health of community-dwelling older adults.